2009
DOI: 10.1080/10410230903263990
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Perceptions of Physicians' Communication: The Relationship Among Communication Practices, Satisfaction, and Collaboration

Abstract: This study examined the relationships among nurses' perceptions of physician communication practices, nurse-physician collaboration, and nurses' job satisfaction. Two hundred five nurses employed at a pediatric hospital completed surveys on site that examined perceptions of nurse-physician and physician-patient communication, job satisfaction, and nurse-physician collaboration. Nurse reports of physicians who listened effectively and used clear, humorous, immediate, and empathic messages were strongly related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
0
38
0
2
Order By: Relevance
“…In fact, the lack of time to foster meaningful relationships may contribute to the physician-nurse tension highlighted in the narratives (Rushton et al 2013). Physician-nurse communication is further complicated by issues of professional identity, power, and institutional culture (Wanzer, Wojtaszczyk, and Kelly 2009) and may be even more complex when the physician is a trainee. Collaborative practice training may help physicians and nurses build cross-discipline team identities (Bartunek 2011), diminishing differences, establishing support mechanisms, and improving patient care.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the lack of time to foster meaningful relationships may contribute to the physician-nurse tension highlighted in the narratives (Rushton et al 2013). Physician-nurse communication is further complicated by issues of professional identity, power, and institutional culture (Wanzer, Wojtaszczyk, and Kelly 2009) and may be even more complex when the physician is a trainee. Collaborative practice training may help physicians and nurses build cross-discipline team identities (Bartunek 2011), diminishing differences, establishing support mechanisms, and improving patient care.…”
Section: Discussionmentioning
confidence: 97%
“…Historically, interactions between physicians and RNs have been fraught with tension. 12,13 Research indicates that physicians are perceived to be at the top of the health professions hierarchy. 12 At times, physicians have maintained a patriarchal or dominant position, whereas those in the nursing profession have been viewed as occupying a less prestigious, or even subservient, role.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 Research indicates that physicians are perceived to be at the top of the health professions hierarchy. 12 At times, physicians have maintained a patriarchal or dominant position, whereas those in the nursing profession have been viewed as occupying a less prestigious, or even subservient, role. 14,15 Even research focused exclusively on nurse practitioner (NP)-physician relationships shows that some physicians believe they provide higher-quality clinical examinations and consultations during primary care visits than do NPs.…”
Section: Discussionmentioning
confidence: 98%
“…Accomplishing these goals may be particularly challenging when IP healthcare teams are composed of professionals with little prior experience working with team members from different disciplines (Barr, Hammick, Koppel & Reeves, 1999), as is often the case. Functioning effectively within an IP healthcare team may require individuals to develop skills beyond their traditional specialty training and education (Nembhard & Edmondson, 2006;Wanzer, Wojtaszczyk & Kelly, 2009). Effective communication among these IP team members is critical to the realization of team goals for safe, high-quality patient care.…”
Section: Introductionmentioning
confidence: 99%
“…To address this and improve our educational process we identified existing models for communication among healthcare professionals (Apker, Propp, Zabava Ford, & Hofmeister, 2006;Boaro, Fancott, Baker, Velji & Andreoli, 2010;Ellingson, 2003;Wanzer et al, 2009), yet found little guidance for models of communication among IP healthcare teams which included patients as team members. Given the increasing emphasis on patient-centered care in many aspects of health care delivery, we believe that IPE should specifically address the inclusion of patients as part of the IP team.…”
Section: Introductionmentioning
confidence: 99%